Implementasi High Availability Cluster Web Server Menggunakan Virtualisasi Container Docker - Putra, Muhammad Aldi Aditia; Fitri, Iskandar; Iskandar, Agus (STMIK Budi Darma, 2020)
The increasing demand for information on the internet causes the traffic load on the web server to increase. Therefore it can cause the workload on a web server service to be overloaded (request), so that the server is down (overloaded). Based on previous research the application of load balancing can reduce the burden of traffic on the web server. This research method uses load balancing on servers with round robin algorithm and least connections as well as a single server as a comparison. The parameters measured are throughput, responses time, requests per second, CPU utilization. From the test results obtained Haproxy load balancing system, the least connection algorithm is superior to the round robin algorithm. Generated per-second request value of 2607,141 req / s and throughput of 9.25 MB / s for the least connection, while 2807,171 req / s and 9.30 MB / s for round robin.